Federalism As a Tool for Ethnic Conflict Resolution: A Case Study of Iraq - Ababakr, Amer (Mediterranean Journal of Social Sciences, 2022)
Due to ethnic, linguistic and cultural diversities, there is potential for ethnic conflicts and ethnic tensions in community, but the emergence and occurrence of ethnic conflicts depend on the state's approach to managing or suppressing ethnic, linguistic, and cultural variations. Federalism is one of the most important mechanisms that governments adopt to manage ethnic, linguistic and cultural diversities. But the function of federalism in reducing ethnic conflicts is not necessarily positive, and in some cases, it has led to an escalation of ethnic conflicts. Accordingly, the central question is to examine whether federalism is a system to resolve or reduce ethnic conflicts? With an emphasis on ethnic conflicts in Iraq. The research hypothesis is that federalism, through the creation of bureaucratic structures, the development of political parties, the identification, and acceptance of cultural and linguistic commonalities, will restrict and reduce ethnic violence and conflict but not necessarily ethnic protest. Received: 26 December 2021 / Accepted: 28 February 2022 / Published: 5 March 2022